Upaya Peningkatan Partisipasi Masyarakat dalam Penelolaan Sampah di Pasar Tradisional Padang Sappa Kecamatan Ponrang Kabupaten Luwu - Yusuf, Natalie; Rahman, Rahmawati; Yahya, Ilham (Fakultas Teknik Universitas Bosowa, 2024)
Abstract. The Padang Sappa Traditional Market in Ponrang District, Luwu Regency, has a waste management problem, and the surrounding community is still underrepresented in garbage management, which has an adverse effect on the market's ecology. In an effort to promote community involvement in trash management in the Padang Sappa Traditional Market, Ponrang District, Luwu Regency, this study aims to pinpoint the reasons for low community participation. Both quantitative and qualitative (descriptive) data analysis are used in this study. To identify the influential elements, quantitative analysis using the Chi Square test (chi square) with a significant value of 0.05 (a = 0.05) was employed, while to find out efforts to increase community participation in waste management descriptive analysis was used using source triangulation method, theory, policy and the results of the analysis of the most influential factors. According to the analysis's findings, the level of education and employment/income, with values of sig=0.000 and a=0.05, are the variables that have the greatest impact on community participation in waste management. While outreach initiatives are used to enhance community involvement in trash management, the government also plays a role by establishing tight regulations and good infrastructure.